Optimal. Leaf size=23 \[ e^{x+\frac {x}{2-x}}+\log \left ((26-\log (x))^2\right ) \]
________________________________________________________________________________________
Rubi [F] time = 2.17, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {8-8 x+2 x^2+e^{\frac {-3 x+x^2}{-2+x}} \left (-156 x+104 x^2-26 x^3\right )+e^{\frac {-3 x+x^2}{-2+x}} \left (6 x-4 x^2+x^3\right ) \log (x)}{-104 x+104 x^2-26 x^3+\left (4 x-4 x^2+x^3\right ) \log (x)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-8+8 x-2 x^2-e^{\frac {-3 x+x^2}{-2+x}} \left (-156 x+104 x^2-26 x^3\right )-e^{\frac {-3 x+x^2}{-2+x}} \left (6 x-4 x^2+x^3\right ) \log (x)}{(2-x)^2 x (26-\log (x))} \, dx\\ &=\int \left (\frac {e^{\frac {(-3+x) x}{-2+x}} \left (6-4 x+x^2\right )}{(-2+x)^2}-\frac {8}{(-2+x)^2 (-26+\log (x))}+\frac {8}{(-2+x)^2 x (-26+\log (x))}+\frac {2 x}{(-2+x)^2 (-26+\log (x))}\right ) \, dx\\ &=2 \int \frac {x}{(-2+x)^2 (-26+\log (x))} \, dx-8 \int \frac {1}{(-2+x)^2 (-26+\log (x))} \, dx+8 \int \frac {1}{(-2+x)^2 x (-26+\log (x))} \, dx+\int \frac {e^{\frac {(-3+x) x}{-2+x}} \left (6-4 x+x^2\right )}{(-2+x)^2} \, dx\\ &=e^{\frac {(3-x) x}{2-x}}+2 \int \frac {x}{(-2+x)^2 (-26+\log (x))} \, dx-8 \int \frac {1}{(-2+x)^2 (-26+\log (x))} \, dx+8 \int \frac {1}{(-2+x)^2 x (-26+\log (x))} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.11, size = 22, normalized size = 0.96 \begin {gather*} e^{-1-\frac {2}{-2+x}+x}+2 \log (26-\log (x)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.76, size = 22, normalized size = 0.96 \begin {gather*} e^{\left (\frac {x^{2} - 3 \, x}{x - 2}\right )} + 2 \, \log \left (\log \relax (x) - 26\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.25, size = 22, normalized size = 0.96 \begin {gather*} e^{\left (\frac {x^{2} - 3 \, x}{x - 2}\right )} + 2 \, \log \left (\log \relax (x) - 26\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.14, size = 20, normalized size = 0.87
method | result | size |
risch | \({\mathrm e}^{\frac {x \left (x -3\right )}{x -2}}+2 \ln \left (-26+\ln \relax (x )\right )\) | \(20\) |
default | \(2 \ln \left (-26+\ln \relax (x )\right )+\frac {x \,{\mathrm e}^{\frac {x^{2}-3 x}{x -2}}-2 \,{\mathrm e}^{\frac {x^{2}-3 x}{x -2}}}{x -2}\) | \(48\) |
norman | \(2 \ln \left (-26+\ln \relax (x )\right )+\frac {x \,{\mathrm e}^{\frac {x^{2}-3 x}{x -2}}-2 \,{\mathrm e}^{\frac {x^{2}-3 x}{x -2}}}{x -2}\) | \(48\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.40, size = 19, normalized size = 0.83 \begin {gather*} e^{\left (x - \frac {2}{x - 2} - 1\right )} + 2 \, \log \left (\log \relax (x) - 26\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.64, size = 28, normalized size = 1.22 \begin {gather*} 2\,\ln \left (\ln \relax (x)-26\right )+{\mathrm {e}}^{-\frac {3\,x}{x-2}}\,{\mathrm {e}}^{\frac {x^2}{x-2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.46, size = 19, normalized size = 0.83 \begin {gather*} e^{\frac {x^{2} - 3 x}{x - 2}} + 2 \log {\left (\log {\relax (x )} - 26 \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________